Evaluation of the reduction in carbonyl emissions and ozone formation potential from the exhaust of a heavy-duty diesel engine by hydrogen-diesel dual fuel combustion. (5th March 2018) - Jhang, Syu-Ruei; Chen, Kang-Shin; Lin, Sheng-Lun; Lin, Yuan-Chung; Amesho, Kassian T.T.; Chen, Chung-Bang
Highlights: Diesel-H2 dual fuel combustion reduce total and individual carbonyl compounds. Higher carbonyl compounds occurred at idle, and decreased with the engine loads. The ozone formation potential was strongly reduced with use of hydrogen. The maximum reduction for formaldehyde with 1.20% H2 volume fraction at 75% load. H2 addition can efficiently reduce the ozone formation potential. Abstract: In this study, diesel engine was fueled by multi-fuels, including conventional diesel and 0, 0.6 and 1.2 vol% hydrogen and operated at low to high engine loads. Low molecular weight carbonyls, such as formaldehyde, acetaldehyde, and acetone, contributed 79.2–87.2% of total carbonyl compounds which are the more prominent when the engine operated at low load. With 0.6 and 1.2 vol% of hydrogen addition, formaldehyde decreased 10.4–10.9% at idling condition. As the load increases 25, 50 and 75%, the formaldehyde decreased by 2.93–25.1, 5.91–25.8 and 2.28–40.5%, respectively. The same reduction phenomenon can also be observed from acrolein, acetone, propionaldehyde, crotonaldehyde and 2-butanone & butyraldehyde emissions. The highest ozone-formation potential (OFP) from multi-pollution emissions was found at idling operation. The high OFP could be reduced by increasing hydrogen additions and eventually approached the lowest level with 1.2 vol% hydrogen addition at middle to high engine load. Nevertheless, the diesel engine with hydrogen addition could reduce a certain amount of CBC emission and OFP at engine idling operation.